Doctor-patient communication in medicine and dental medicine - Sinadinović Danka; Aleksić-Hajduković Irena; Mijomanović Stevan (Serbian Medical Society - Dental Section, Belgrade, 2020)
Doctor-patient communication is a type of institutional communication which distinct linguistic features can significantly affect patient satisfaction and treatment outcome. A medical encounter has a clearly defined structure that has been shifting from clinician-centred to patient-centred. Therefore, it is of utter importance for prospective doctors and dentists to be aware of the role of language when communicating with their patients. Given the fact that working in a medical/dental practice has become increasingly international, the paper focuses on the role of the English language. New communicative models and environments such as Computer-Mediated Medical Communication (CMMC) and Video Interaction Guidance (VIG) are also presented.